Business Intelligence Dashboard for Financial Performance Analysis of Public Service Agency Using Microsoft Power BI - Larasati, Damayanti; Tanzil, Nanny Dewi; Alfian, Adhi; Wardani, Lindawati (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2024)
This research discusses the use of business intelligence dashboard for financial performance analysis at the BRIN Technology Service Center Public Service Agency, focusing on the decrease of BLU cash balance. The factors that affect the ups and downs of the BLU cash balance are the total revenue realization and the total revenue expenditure realization in the current year. Business Intelligence (BI) is one of the tools that allows organizations to access and analyze data and information to improve and optimize decisions and performance. In Indonesia, there has not been much research related to the implementation of business intelligence dashboards for financial performance analysis in public service agencies. The research aims to create a business intelligence dashboard that can provide insight to leaders in making decisions to increase BLU cash balances. This research uses a qualitative descriptive method, and the system development method uses a business intelligence roadmap approach. The result of this research is that with the help of the BI dashboard, executives can gain insight to increase Blu's cash balance, improvements in receivables management are needed and they need to be more selective in choosing partners who use technology services.